1994
DOI: 10.1111/j.1439-0418.1994.tb00814.x
|View full text |Cite
|
Sign up to set email alerts
|

Demographical parameters of Frankliniella occidentalis (Pergande) (Thysanoptera, Thripidae)

Abstract: In less than 3 years (1986–1988) Frankliniella occidentalis, imported from USA, had spread throughout Europe. It is a polyphagous Thysanoptera which causes important yield loss in greenhouses, in both vegetable and ornamental crops. However, insufficient data are available on its basic biology. The purpose of this work was thus to establish its life table. A cohort of 95 individuals were observed daily during their whole lifetime. The development time is short, 14.2 days, and no significant difference has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
3

Year Published

1997
1997
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 4 publications
1
20
0
3
Order By: Relevance
“…Values of r m of F. occidentalis at 25 C as reported in literature are: 0.17 day ,1 on susceptible cucumber cv. Corona (van Rijn et al, 1995), 0.157 day ,1 on a susceptible cotton variety (Trichilo & Leigh, 1988), 0.14 day ,1 on bean (Brødsgaard, 1991;Gerin et al, 1994), 0.171 day ,1 on chrysanthemum (Robb, 1989), 0.127 day ,1 on petunia (Wijkamp, 1995) and 0.02 day ,1 on peanut (Lowry et al, 1992). In the present study negative values for r r were found on the most resistant cucumber accessions, especially for population NZ.…”
Section: Discussionmentioning
confidence: 99%
“…Values of r m of F. occidentalis at 25 C as reported in literature are: 0.17 day ,1 on susceptible cucumber cv. Corona (van Rijn et al, 1995), 0.157 day ,1 on a susceptible cotton variety (Trichilo & Leigh, 1988), 0.14 day ,1 on bean (Brødsgaard, 1991;Gerin et al, 1994), 0.171 day ,1 on chrysanthemum (Robb, 1989), 0.127 day ,1 on petunia (Wijkamp, 1995) and 0.02 day ,1 on peanut (Lowry et al, 1992). In the present study negative values for r r were found on the most resistant cucumber accessions, especially for population NZ.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially the case with second-instar thrips, as the subsequent stage (the prepupa) does not remain on the leaf and begin the acquisition process anew. Gerin et al (1994) reported that the duration of the second-instar of western Xower thrips reared on beans at 25°C is ca. 3 days (73.4 h).…”
Section: Age Of Inoculum a (H)mentioning
confidence: 99%
“…Previous life‐history studies have investigated the development and reproduction of F. occidentalis on many different plants, including bean (Brødsgaard, 1994; Gerin et al., 1994), chrysanthemum (Robb & Parrella, 1991), cotton (Trichilo & Leigh, 1988), cucumber (Gaum et al., 1994; van Rijn et al., 1995; de Kogel et al., 1997; Hulshof et al., 2003), and peanut (Lowry et al., 1992). In these experiments, thrips were tested either on whole plants (on which they may have fed on any plant part) or on leaves only.…”
Section: Introductionmentioning
confidence: 99%